Study the Relation of Copeptin and Some Biochemical Parameters in with Obesity in Kirkuk City - Iman Abbas Ghaeb Al-Bayati; Salam Shihab Ahmed; Hassan Ismail Sultan (Institute of Medico-legal Publications Pvt Ltd, 2021)
In this Case-Control Study, One hundred thirty six adult subjects with obesity were separated to take partin the current research. At the Kirkuk General Hospital in Kirkuk City- Iraq, Applying this study had donefor the duration of the 16th of February to the end of June 2020 Adult subjects with obesity outpatientattended to Kirkuk General Hospital were enrolled in this research. Ages of adult persons were amid 18 to62 years and they were from the center and periphery of Kirkuk City. Thirty one adult persons with obesitywere considered as a study group, thirty adult persons were measured as control, sixty-three adult personsdidn’t assembly the inclusion criteria and 20 adult persons refuse to participate in this study because of thein agreement of their people. Blood sample were collected from each adult person for determination ofcopepetin, lipid profile and blood sugar determination. The study revealed that the mean of copeptin washigher in obese group as compared with healthy control group (166.4±81.8 vs. 35.01±12.3 pg/ml). Thestudy showed a significant difference between obese and the control group regarding fasting blood sugar(FBS) (119.3±12.5 and 98.2±11.6 mg/dl) respectively. The study showed that, the mean serum triglyceridewas recorded to be higher in obese group (110.4±45.3 mg/dl) as compared with healthy control group (90.9±29.1 mg/dl). The study showed that, the mean of serum cholesterol was higher in obese group (170.7±36.3mg/dl) as compared with healthy control group (151.7 ±29.6 mg/dl). The study showed that, the lowestmean of serum HDL was recorded in obese group (41.6±14.5 mg/dl) as compared with healthy control group(61.44 ±7.63 mg/dl). The study showed that, the highest mean of serum LDL and VLDL was recorded inobese group as compared with healthy control group. The study showed negative correlation between serumcopeptin and FBS in obese individuals. It was concluded that, Serum copeptin was significantly higher inobese group as compared with healthy control group and there was a negative correlation between copeptinand blood sugar levels